Powder composition for cement addition and preparation process thereof

By adopting powder compositions with modified sodium lignin sulfonate, modified polycarboxylic acid water reducer and other components, the problem that existing cement additives are difficult to improve the permeability and water resistance of cement concrete at the same time, and the comprehensive improvement of cement concrete performance is achieved.

CN119569371APending Publication Date: 2025-03-07YUNNAN SUYUAN NEW MATERIAL CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411758509.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

It is difficult for existing cement additives to improve the permeability and water resistance of cement concrete at the same time.

Method used

The powder compositions of modified sodium lignin sulfonate, modified polycarboxylic acid water reducing agent, modified anti-seepage component, composite anti-freeze component, gypsum-based water-resistant agent component, composite anti-mold component and rust inhibitor component are used to improve the performance of these components through a specific preparation process.

Benefits of technology

It significantly improves the fluidity, seepage resistance, frost resistance, water resistance, mildew resistance and rust resistance of cement concrete, and enhances the overall performance of concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005166969880000101
    Figure BDA0005166969880000101
Patent Text Reader

Abstract

The invention relates to the technical field of cement additives, in particular to a powder composition for cement addition and a preparation process of the powder composition, modified sodium lignin sulfonate serves as an important component of the powder composition, dispersity and stability of sodium lignin sulfonate are effectively improved through sulfomethylation and condensation reaction, and in cement concrete, the powder composition has the advantages that the dispersity and stability of sodium lignin sulfonate are improved; the modified sodium lignin sulfonate can be adsorbed on the surfaces of cement particles to form a protective film, friction force and resistance among the cement particles can be reduced, so that the fluidity of the concrete is improved, meanwhile, a sulfomethylation structure of the modified sodium lignin sulfonate can chemically react with calcium ions in the cement to form stable calcium salt, the stability of the concrete is further enhanced, and the service life of the concrete is prolonged. According to the powder composition for cement addition and the preparation method of the powder composition, the performance of cement concrete can be remarkably improved through well-designed components, and the composition has excellent flowability, anti-permeability, anti-freezing property, water resistance, mildew resistance and rust resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cement additives, and in particular to a powder composition for cement additives and a preparation process thereof. Background Art

[0002] In the field of construction engineering, cement concrete is one of the most important building materials, and its performance directly affects the quality and safety of the project. However, traditional cement concrete has problems such as poor fluidity, insufficient impermeability, susceptibility to frost damage, poor water resistance, easy breeding of mold, and easy rust of steel bars. These problems limit the application of cement concrete in certain special environments and also increase the cost and risk of project maintenance.

[0003] In order to solve the above problems, people in the field have been committed to developing new cement additives to improve the performance of cement concrete. Among them, lignin sulfonate additives are widely used because of their excellent dispersibility and water-reducing effect. However, traditional lignin sulfonate additives still need to be improved in performance, especially in terms of impermeability, frost resistance, water resistance and mildew resistance. In addition, polycarboxylic acid water reducers, as a high-performance concrete admixture, have received extensive attention and application in recent years. Polycarboxylic acid water reducers have the advantages of good dispersibility, high water reduction rate, and significant improvement in concrete strength, but their preparation cost is relatively high, and their performance under certain special environments (such as low temperature and humid environment) still needs to be improved. In order to solve the above problems, the present invention proposes a novel preparation process of cement additive powder composition, so that the prepared additive can improve the performance of cement concrete. Summary of the invention

[0004] Technical issues solved

[0005] In view of the above-mentioned shortcomings of the prior art, the present invention provides a powder composition for cement additive and a preparation process thereof, which can effectively solve the problem that the additives in the prior art cannot simultaneously improve the impermeability and water resistance of cement concrete.

[0006] Technical Solution

[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0008] A powder composition for cement addition, the powder composition for cement addition consisting of the following components: modified sodium lignin sulfonate, modified polycarboxylic acid water reducer, modified anti-seepage agent component, composite antifreeze agent component, gypsum-based water-resistant agent component, composite mildew inhibitor component and rust inhibitor component;

[0009] The modified sodium lignin sulfonate is prepared by subjecting sodium lignin sulfonate to sulfomethylation and condensation reactions;

[0010] The modified polycarboxylate water reducer is prepared with calcium lignin sulfonate and polyethylene glycol as main synthetic raw materials;

[0011] The modified anti-seepage agent component is prepared by compounding metakaolin with ultrafine fly ash after being modified by a silane coupling agent;

[0012] The composite antifreeze component is prepared by compounding a plurality of inorganic salt antifreeze agents.

[0013] Furthermore, the preparation steps of the modified sodium lignin sulfonate are:

[0014] Step 1, weigh 4 g of formaldehyde, 15 g of sodium sulfite and 200 g of deionized water into a beaker, stir and disperse in a water bath at 80° C., and the obtained mixture is recorded as a sulfomethylation component;

[0015] Step 2, weigh 10g of sodium lignin sulfonate and 150g of deionized water into a beaker, mix and stir in a water bath at 50°C, and adjust the pH value to 10 with a 10% sodium hydroxide solution. The result is recorded as the component to be modified;

[0016] Step 3: adding the sulfomethylation component to the component to be modified at a rate of 2 drops / s, reacting for 2 hours, adjusting to neutrality with a 5% hydrochloric acid solution, and drying in vacuum to obtain sodium lignin sulfonate.

[0017] Furthermore, the specific operation of stirring and dispersing in step 1 is stirring at a stirring speed of 500 r / min for 30 min, and the specific operation of mixing and stirring in step 2 is stirring at a stirring speed of 300 r / min for 30 min.

[0018] Furthermore, the preparation steps of the modified polycarboxylate water-reducing agent are:

[0019] Step A, pour 50g of polyethylene glycol into a three-necked flask and heat it in a water bath to 80°C, add 5g of maleic anhydride and 1g of p-toluenesulfonic acid through a dropping funnel at a dropping rate of 1 drop / s, and react at a constant temperature for 1h after the dropping is completed. The result is recorded as the reaction system;

[0020] Step B: add 3.6 g acrylamide, 21 g calcium lignin sulfonate, 1.8 g ammonium persulfate and 150 mL deionized water to the reaction system, react in a water bath at 80° C. for 4 h, and then vacuum dry to obtain a modified polycarboxylate water reducer.

[0021] Furthermore, the preparation method of the modified anti-seepage agent component is:

[0022] The metakaolin was ground through a 200-mesh sieve and poured into a vertical disperser. After adding 5% by weight of silane coupling agent KH-560, it was dispersed at a speed of 300 r / min for 15 minutes. Then, ultrafine fly ash was added at a weight of 30% of the metakaolin and continued to disperse at the original speed for 15 minutes. The result was the modified anti-seepage agent component.

[0023] Furthermore, the preparation method of the composite antifreeze component is:

[0024] Calcium chloride, sodium chloride, magnesium chloride and sodium carbonate are weighed in equal weight ratios, mixed, and stirred at a stirring speed of 200 r / min for 5 minutes to obtain a composite antifreeze component.

[0025] Furthermore, the preparation method of the gypsum-based water-resistant agent component is:

[0026] Mix 3g of sodium methyl silicate and 100g of deionized water, stir at a stirring speed of 500r / min for 10min, then add 60-80g of gypsum powder, stir at a stirring speed of 100r / min for 10min, dry at 68°C to constant weight, and grind through a 200-mesh sieve to obtain the gypsum-based water-resistant agent component.

[0027] Furthermore, the composite mildew inhibitor component is prepared by mixing dodecyltrimethylammonium chloride powder, tetradecyltrimethylammonium chloride powder and copper oxide powder in an equal weight ratio.

[0028] Furthermore, the rust inhibitor is sodium nitrite.

[0029] A preparation process of a powder composition for cement addition, the preparation process comprising:

[0030] 4-5 parts of modified sodium lignin sulfonate, 5-6 parts of modified polycarboxylic acid water reducer, 3-4 parts of modified anti-seepage agent component, 2-3 parts of composite antifreeze agent component, 6-8 parts of gypsum-based water-resistant agent component, 2-3 parts of composite mildew inhibitor component and 1-2 parts of rust inhibitor component are weighed according to weight, poured into a vertical disperser, and dispersed at a speed of 200-300 r / min for 30 minutes to obtain a powder composition for cement addition.

[0031] Beneficial Effects

[0032] The present invention provides a powder composition for cement additive and a preparation process thereof. Compared with the prior art, the present invention has the following beneficial effects:

[0033] 1. The modified sodium lignin sulfonate in the present invention is an important component of the present invention. Through sulfomethylation and condensation reaction, the dispersibility and stability of sodium lignin sulfonate are effectively improved. In cement concrete, the modified sodium lignin sulfonate can be adsorbed on the surface of cement particles to form a protective film, which can reduce the friction and resistance between cement particles, thereby improving the fluidity of concrete. At the same time, its sulfomethylation structure can chemically react with calcium ions in cement to form stable calcium salts, further enhancing the stability of concrete. The modified polycarboxylate water reducer in the present invention is prepared by using calcium lignin sulfonate and polyethylene glycol as main synthetic raw materials under specific reaction conditions. The water reducer has excellent dispersibility and water-reducing effect, can significantly reduce the water-cement ratio of concrete, and improve the strength and durability of concrete. Its mechanism of action is that the long chain structure of polyethylene glycol can increase the spatial distance between cement particles and reduce the interaction force between particles, while calcium lignin sulfonate can enhance this dispersion effect, making the concrete more uniform and dense.

[0034] 2. The modified anti-seepage agent component in the present invention is prepared by compounding metakaolin with ultrafine fly ash after being modified by silane coupling agent. After the metakaolin is ground and modified by silane coupling agent, its surface properties are significantly improved, and it can better combine with the cement matrix to form a dense anti-seepage layer. The addition of ultrafine fly ash can further enhance the anti-seepage effect, making it difficult for concrete to leak when subjected to water pressure; the composite antifreeze agent component is compounded by a variety of inorganic salt antifreeze agents and has an excellent antifreeze effect. Under low temperature conditions, these inorganic salts can lower the freezing point of water and prevent the water in the concrete from freezing and expanding to cause structural damage. At the same time, they can also promote the hydration reaction of cement and improve the early strength of concrete; the sodium methyl silicate in the gypsum-based water-resistant agent component can form a dense waterproof layer on the surface of the concrete, effectively preventing water from penetrating into the interior of the concrete, and the addition of gypsum powder can enhance the waterproof effect, so that the concrete can still maintain its strength and stability in a humid environment.

[0035] 3. The addition of the composite mildew inhibitor component in the present invention can destroy the cell wall and cell membrane of the mold, inhibit its growth and reproduction, and can also combine with the organic matter in the concrete to form a mildew-proof layer to further prevent the invasion and reproduction of mildew; the rust inhibitor component can form a protective film with the surface of the steel bars in the concrete to prevent the steel bars from rusting; the cement additive powder composition of the present invention can significantly improve the performance of cement concrete through carefully designed components and its preparation method. The composition has excellent fluidity, impermeability, frost resistance, water resistance, mildew resistance and rust resistance, and can be widely used in various construction projects, providing a strong guarantee for the quality and safety of construction projects. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] The present invention will be further described below in conjunction with the embodiments.

[0038] Example 1

[0039] A cement additive powder composition of this embodiment, the cement additive powder composition is composed of the following components: modified sodium lignin sulfonate, modified polycarboxylic acid water reducer, modified anti-seepage agent component, composite antifreeze agent component, gypsum-based water-resistant agent component, composite mildew inhibitor component and rust inhibitor component;

[0040] Modified sodium lignin sulfonate is prepared by sulfomethylation and condensation reaction of sodium lignin sulfonate. The specific preparation steps are as follows:

[0041] Step 1, weigh 4 g of formaldehyde, 15 g of sodium sulfite and 200 g of deionized water into a beaker, stir at a stirring speed of 500 r / min for 30 min in a water bath at 80° C., and the obtained mixture is recorded as a sulfomethylation component;

[0042] Step 2, weigh 10g of sodium lignin sulfonate and 150g of deionized water into a beaker, stir at a stirring speed of 300r / min for 30min in a water bath at 50°C, and adjust the pH value to 10 with a 10% sodium hydroxide solution, and the result is recorded as the component to be modified;

[0043] Step 3: adding the sulfomethylation component to the component to be modified at a rate of 2 drops / s, reacting for 2 hours, adjusting to neutrality with a 5% hydrochloric acid solution, and drying in vacuum to obtain sodium lignin sulfonate.

[0044] The modified polycarboxylate water reducer is prepared with calcium lignin sulfonate and polyethylene glycol as the main synthetic raw materials. The specific preparation steps are as follows:

[0045] Step A, pour 50g of polyethylene glycol into a three-necked flask and heat it in a water bath to 80°C, add 5g of maleic anhydride and 1g of p-toluenesulfonic acid through a dropping funnel at a dropping rate of 1 drop / s, and react at a constant temperature for 1h after the dropping is completed. The result is recorded as the reaction system;

[0046] Step B: add 3.6 g acrylamide, 21 g calcium lignin sulfonate, 1.8 g ammonium persulfate and 150 mL deionized water to the reaction system, react in a water bath at 80° C. for 4 h, and then vacuum dry to obtain a modified polycarboxylate water reducer.

[0047] The modified anti-seepage agent component is prepared by compounding metakaolin with ultrafine fly ash after being modified by a silane coupling agent. The specific preparation method is as follows:

[0048] The metakaolin was ground through a 200-mesh sieve and poured into a vertical disperser. After adding 5% by weight of silane coupling agent KH-560, it was dispersed at a speed of 300 r / min for 15 minutes. Then, ultrafine fly ash was added at a weight of 30% of the metakaolin and continued to disperse at the original speed for 15 minutes. The result was the modified anti-seepage agent component.

[0049] The composite antifreeze component is prepared by compounding a variety of inorganic salt antifreeze agents, and the specific preparation method is as follows:

[0050] Calcium chloride, sodium chloride, magnesium chloride and sodium carbonate are weighed in equal weight ratios, mixed, and stirred at a stirring speed of 200 r / min for 5 minutes to obtain a composite antifreeze component.

[0051] The preparation method of the gypsum-based water-proofing agent component is:

[0052] Mix 3g of sodium methyl silicate and 100g of deionized water, stir at a stirring speed of 500r / min for 10min, then add 60g of gypsum powder, stir at a stirring speed of 100r / min for 10min, dry at 68°C to constant weight, and grind through a 200-mesh sieve to obtain the gypsum-based water-resistant agent component.

[0053] The composite mildew inhibitor is prepared by mixing dodecyl trimethyl ammonium chloride powder, tetradecyl trimethyl ammonium chloride powder and copper oxide powder in equal weight ratios, and the rust inhibitor is sodium nitrite.

[0054] A preparation process of a powder composition for cement addition, the preparation process comprising:

[0055] 4 parts of modified sodium lignin sulfonate, 5 parts of modified polycarboxylic acid water reducer, 3 parts of modified anti-seepage agent component, 2 parts of composite antifreeze agent component, 6 parts of gypsum-based water-resistant agent component, 2 parts of composite mildew inhibitor component and 1 part of rust inhibitor component were weighed according to weight and poured into a vertical disperser, and dispersed at a speed of 200 r / min for 30 minutes to obtain a powder composition for cement addition.

[0056] Example 2

[0057] A cement additive powder composition of this embodiment, the cement additive powder composition is composed of the following components: modified sodium lignin sulfonate, modified polycarboxylic acid water reducer, modified anti-seepage agent component, composite antifreeze agent component, gypsum-based water-resistant agent component, composite mildew inhibitor component and rust inhibitor component;

[0058] Modified sodium lignin sulfonate is prepared by sulfomethylation and condensation reaction of sodium lignin sulfonate. The specific preparation steps are as follows:

[0059] Step 1, weigh 4 g of formaldehyde, 15 g of sodium sulfite and 200 g of deionized water into a beaker, stir at a stirring speed of 500 r / min for 30 min in a water bath at 80° C., and the obtained mixture is recorded as a sulfomethylation component;

[0060] Step 2, weigh 10g of sodium lignin sulfonate and 150g of deionized water into a beaker, stir at a stirring speed of 300r / min for 30min in a water bath at 50°C, and adjust the pH value to 10 with a 10% sodium hydroxide solution, and the result is recorded as the component to be modified;

[0061] Step 3: adding the sulfomethylation component to the component to be modified at a rate of 2 drops / s, reacting for 2 hours, adjusting to neutrality with a 5% hydrochloric acid solution, and drying in vacuum to obtain sodium lignin sulfonate.

[0062] The modified polycarboxylate water reducer is prepared with calcium lignin sulfonate and polyethylene glycol as the main synthetic raw materials. The specific preparation steps are as follows:

[0063] Step A, pour 50g of polyethylene glycol into a three-necked flask and heat it in a water bath to 80°C, add 5g of maleic anhydride and 1g of p-toluenesulfonic acid through a dropping funnel at a dropping rate of 1 drop / s, and react at a constant temperature for 1h after the dropping is completed. The result is recorded as the reaction system;

[0064] Step B: add 3.6 g acrylamide, 21 g calcium lignin sulfonate, 1.8 g ammonium persulfate and 150 mL deionized water to the reaction system, react in a water bath at 80° C. for 4 h, and then vacuum dry to obtain a modified polycarboxylate water reducer.

[0065] The modified anti-seepage agent component is prepared by compounding metakaolin with ultrafine fly ash after being modified by a silane coupling agent. The specific preparation method is as follows:

[0066] The metakaolin was ground through a 200-mesh sieve and poured into a vertical disperser. After adding 5% by weight of silane coupling agent KH-560, it was dispersed at a speed of 300 r / min for 15 minutes. Then, ultrafine fly ash was added at a weight of 30% of the metakaolin and continued to disperse at the original speed for 15 minutes. The result was the modified anti-seepage agent component.

[0067] The composite antifreeze component is prepared by compounding a variety of inorganic salt antifreeze agents, and the specific preparation method is as follows:

[0068] Calcium chloride, sodium chloride, magnesium chloride and sodium carbonate are weighed in equal weight ratios, mixed, and stirred at a stirring speed of 200 r / min for 5 minutes to obtain a composite antifreeze component.

[0069] The preparation method of the gypsum-based water-proofing agent component is:

[0070] Mix 3g of sodium methyl silicate and 100g of deionized water, stir at a stirring speed of 500r / min for 10min, then add 80g of gypsum powder, stir at a stirring speed of 100r / min for 10min, dry at 68°C to constant weight, and grind through a 200-mesh sieve to obtain the gypsum-based water-resistant agent component.

[0071] The composite mildew inhibitor is prepared by mixing dodecyl trimethyl ammonium chloride powder, tetradecyl trimethyl ammonium chloride powder and copper oxide powder in equal weight ratios, and the rust inhibitor is sodium nitrite.

[0072] A preparation process of a powder composition for cement addition, the preparation process comprising:

[0073] 5 parts of modified sodium lignin sulfonate, 6 parts of modified polycarboxylic acid water reducer, 4 parts of modified anti-seepage agent component, 3 parts of composite antifreeze agent component, 8 parts of gypsum-based water-resistant agent component, 3 parts of composite mildew inhibitor component and 2 parts of rust inhibitor component were weighed according to weight and poured into a vertical disperser, and dispersed at a speed of 300 r / min for 30 minutes to obtain a powder composition for cement addition.

[0074] Example 3

[0075] A cement additive powder composition of this embodiment, the cement additive powder composition is composed of the following components: modified sodium lignin sulfonate, modified polycarboxylic acid water reducer, modified anti-seepage agent component, composite antifreeze agent component, gypsum-based water-resistant agent component, composite mildew inhibitor component and rust inhibitor component;

[0076] Modified sodium lignin sulfonate is prepared by sulfomethylation and condensation reaction of sodium lignin sulfonate. The specific preparation steps are as follows:

[0077] Step 1, weigh 4 g of formaldehyde, 15 g of sodium sulfite and 200 g of deionized water into a beaker, stir at a stirring speed of 500 r / min for 30 min in a water bath at 80° C., and the obtained mixture is recorded as a sulfomethylation component;

[0078] Step 2, weigh 10g of sodium lignin sulfonate and 150g of deionized water into a beaker, stir at a stirring speed of 300r / min for 30min in a water bath at 50°C, and adjust the pH value to 10 with a 10% sodium hydroxide solution, and the result is recorded as the component to be modified;

[0079] Step 3: adding the sulfomethylation component to the component to be modified at a rate of 2 drops / s, reacting for 2 hours, adjusting to neutrality with a 5% hydrochloric acid solution, and drying in vacuum to obtain sodium lignin sulfonate.

[0080] The modified polycarboxylate water reducer is prepared with calcium lignin sulfonate and polyethylene glycol as the main synthetic raw materials. The specific preparation steps are as follows:

[0081] Step A, pour 50g of polyethylene glycol into a three-necked flask and heat it in a water bath to 80°C, add 5g of maleic anhydride and 1g of p-toluenesulfonic acid through a dropping funnel at a dropping rate of 1 drop / s, and react at a constant temperature for 1h after the dropping is completed. The result is recorded as the reaction system;

[0082] Step B: add 3.6 g acrylamide, 21 g calcium lignin sulfonate, 1.8 g ammonium persulfate and 150 mL deionized water to the reaction system, react in a water bath at 80° C. for 4 h, and then vacuum dry to obtain a modified polycarboxylate water reducer.

[0083] The modified anti-seepage agent component is prepared by compounding metakaolin with ultrafine fly ash after being modified by a silane coupling agent. The specific preparation method is as follows:

[0084] The metakaolin was ground through a 200-mesh sieve and poured into a vertical disperser. After adding 5% by weight of silane coupling agent KH-560, it was dispersed at a speed of 300 r / min for 15 minutes. Then, ultrafine fly ash was added at a weight of 30% of the metakaolin and continued to disperse at the original speed for 15 minutes. The result was the modified anti-seepage agent component.

[0085] The composite antifreeze component is prepared by compounding a variety of inorganic salt antifreeze agents, and the specific preparation method is as follows:

[0086] Calcium chloride, sodium chloride, magnesium chloride and sodium carbonate are weighed in equal weight ratios, mixed, and stirred at a stirring speed of 200 r / min for 5 minutes to obtain a composite antifreeze component.

[0087] The preparation method of the gypsum-based water-proofing agent component is:

[0088] Mix 3g of sodium methyl silicate and 100g of deionized water, stir at a stirring speed of 500r / min for 10min, then add 70g of gypsum powder, stir at a stirring speed of 100r / min for 10min, dry at 68°C to constant weight, and grind through a 200-mesh sieve to obtain the gypsum-based water-resistant agent component.

[0089] The composite mildew inhibitor is prepared by mixing dodecyl trimethyl ammonium chloride powder, tetradecyl trimethyl ammonium chloride powder and copper oxide powder in equal weight ratios, and the rust inhibitor is sodium nitrite.

[0090] A preparation process of a powder composition for cement addition, the preparation process comprising:

[0091] 5 parts of modified sodium lignin sulfonate, 5 parts of modified polycarboxylic acid water-reducing agent, 4 parts of modified anti-seepage agent component, 2 parts of composite antifreeze agent component, 7 parts of gypsum-based water-resistant agent component, 3 parts of composite mildew inhibitor component and 2 parts of rust inhibitor component were weighed according to weight parts and poured into a vertical disperser, and dispersed at a speed of 300 r / min for 30 minutes to obtain a powder composition for cement addition.

[0092] Comparative Example 1

[0093] The powder composition for cement additive and the preparation process thereof provided in this comparative example are substantially the same as those in Example 1, with the main difference being that in this comparative example 1, the modified sodium lignin sulfonate in Example 1 is replaced by sodium lignin sulfonate.

[0094] Comparative Example 2

[0095] The powder composition for cement addition and the preparation process thereof provided in this comparative example are substantially the same as those in Example 1, with the main difference being that in this comparative example 2, the modified polycarboxylate water-reducing agent in Example 1 is replaced with a polycarboxylate water-reducing agent of model CP 1200.

[0096] Comparative Example 3

[0097] The powder composition for cement addition and the preparation process thereof provided in this comparative example are substantially the same as those in Example 1, with the main difference being that in this comparative example 3, the modified anti-seepage agent component in Example 1 is replaced with metakaolin.

[0098] Performance Testing

[0099] The powder compositions for cement addition prepared in Examples 1-3 and Comparative Examples 1-3 were added to cement concrete at an addition amount of 5%, and were marked as Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, and Comparative Example 3, respectively. The performance of Examples 1-3 and Comparative Examples 1-3 was then tested. The specific testing methods and test items are as follows:

[0100] 1. The compressive strength of Examples 1-3 and Comparative Examples 1-3 was tested with reference to GB 8076-1997 "Testing the strength of cement paste", and the obtained data are recorded in the following table;

[0101] 2. The anti-seepage strength of Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard of JC 474-2008 "Mortar and Concrete Waterproofing Agents", and the obtained data are recorded in the following table;

[0102] 3. The saturated water absorption of Examples 1-3 and Comparative Examples 1-3 was tested with reference to GB / T 11969-2008 "Test Method for Performance of Autoclaved Aerated Concrete", and the obtained data are recorded in the following table;

[0103] 4. The saturated water absorption of Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard of GB / T 8077-2000 "Measurement of Fluidity of Cement Paste", and the obtained data were recorded in the following table;

[0104]

[0105] It can be seen from the data in the above table that the concrete added with the cement powder composition in Examples 1-3 has better performance, and obviously has more excellent compressive strength, impermeability and water resistance. The higher fluidity of cement paste indicates that the concrete added with the cement powder composition in Examples 1-3 has better dispersibility.

[0106] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0107] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A powder composition for cement addition, characterized in that: The powder composition for cement addition is composed of the following components: modified sodium lignin sulfonate, modified polycarboxylic acid water reducer, modified anti-seepage agent component, composite antifreeze agent component, gypsum-based water-resistant agent component, composite mildew inhibitor component and rust inhibitor component; The modified sodium lignin sulfonate is prepared by subjecting sodium lignin sulfonate to sulfomethylation and condensation reactions; The modified polycarboxylate water reducer is prepared with calcium lignin sulfonate and polyethylene glycol as main synthetic raw materials; The modified anti-seepage agent component is prepared by compounding metakaolin with ultrafine fly ash after being modified by a silane coupling agent; The composite antifreeze component is prepared by compounding a plurality of inorganic salt antifreeze agents.

2. A cement additive powder composition according to claim 1, characterized in that: The preparation steps of the modified sodium lignin sulfonate are: Step 1, weigh 4 g of formaldehyde, 15 g of sodium sulfite and 200 g of deionized water into a beaker, stir and disperse in a water bath at 80° C., and the obtained mixture is recorded as a sulfomethylation component; Step 2, weigh 10g of sodium lignin sulfonate and 150g of deionized water into a beaker, mix and stir in a water bath at 50°C, and adjust the pH value to 10 with a 10% sodium hydroxide solution. The result is recorded as the component to be modified; Step 3: adding the sulfomethylation component to the component to be modified at a rate of 2 drops / s, reacting for 2 hours, adjusting to neutrality with a 5% hydrochloric acid solution, and drying in vacuum to obtain sodium lignin sulfonate.

3. A cement additive powder composition according to claim 2, characterized in that: The specific operation of stirring and dispersing in step 1 is stirring at a stirring speed of 500 r / min for 30 min, and the specific operation of mixing and stirring in step 2 is stirring at a stirring speed of 300 r / min for 30 min.

4. A cement additive powder composition according to claim 1, characterized in that: The preparation steps of the modified polycarboxylate water reducer are: Step A, pour 50g of polyethylene glycol into a three-necked flask and heat it in a water bath to 80°C, add 5g of maleic anhydride and 1g of p-toluenesulfonic acid through a dropping funnel at a dropping rate of 1 drop / s, and react at a constant temperature for 1h after the dropping is completed. The result is recorded as the reaction system; Step B: add 3.6 g acrylamide, 21 g calcium lignin sulfonate, 1.8 g ammonium persulfate and 150 mL deionized water to the reaction system, react in a water bath at 80° C. for 4 h, and then vacuum dry to obtain a modified polycarboxylate water reducer.

5. A cement additive powder composition according to claim 1, characterized in that: The preparation method of the modified anti-seepage agent component is: The metakaolin was ground through a 200-mesh sieve and poured into a vertical disperser. After adding 5% by weight of silane coupling agent KH-560, it was dispersed at a speed of 300 r / min for 15 minutes. Then, ultrafine fly ash was added at a weight of 30% of the metakaolin and continued to disperse at the original speed for 15 minutes. The result was the modified anti-seepage agent component.

6. A cement additive powder composition according to claim 1, characterized in that: The preparation method of the composite antifreeze component is: Calcium chloride, sodium chloride, magnesium chloride and sodium carbonate are weighed in equal weight ratios, mixed, and stirred at a stirring speed of 200 r / min for 5 minutes to obtain a composite antifreeze component.

7. A cement additive powder composition according to claim 1, characterized in that: The preparation method of the gypsum-based water-proofing agent component is: Mix 3g of sodium methyl silicate and 100g of deionized water, stir at a stirring speed of 500r / min for 10min, then add 60-80g of gypsum powder, stir at a stirring speed of 100r / min for 10min, dry at 68°C to constant weight, and grind through a 200-mesh sieve to obtain the gypsum-based water-resistant agent component.

8. A cement additive powder composition according to claim 1, characterized in that: The composite mildew-proofing agent is prepared by mixing dodecyl trimethyl ammonium chloride powder, tetradecyl trimethyl ammonium chloride powder and copper oxide powder in equal weight ratios.

9. A cement additive powder composition according to claim 1, characterized in that: The rust inhibitor is sodium nitrite.

10. A process for preparing a powder composition for cement addition according to any one of claims 1 to 9, characterized in that: The preparation process is: 4-5 parts of modified sodium lignin sulfonate, 5-6 parts of modified polycarboxylic acid water reducer, 3-4 parts of modified anti-seepage agent component, 2-3 parts of composite antifreeze agent component, 6-8 parts of gypsum-based water-resistant agent component, 2-3 parts of composite mildew inhibitor component and 1-2 parts of rust inhibitor component are weighed according to weight, poured into a vertical disperser, and dispersed at a speed of 200-300 r / min for 30 minutes to obtain a powder composition for cement addition.

Citation Information

Cited By

  • Calcium-based dry desulfurization agent as well as preparation method and application thereof

    CN120361718A